Effectiveness of Bio-Energy Power to Improving VO2Max Futsal Players - Mashuri, Hendra; Artanayasa, I Wayan (UNIVERSITAS NEGERI MAKASSAR, 2021)
Bio energy power (BEP) is an practice method that combines breathing and exercise to improve the quality of body cells for optimal body performance. Futsal is an aerobic game that requires oxygen in the formation of energy. Increased VO2Max will help the performance of futsal players. The purpose of this study to test the effectiveness of the BEP to the increase in VO2max futsal players beginners. This research is an experimental quantitative research. The study population was a beginner futsal players aged 10-12. The research sample used 30 futsal players. Signification test using paired t-test. The results of the research significance test showed that the t-count value was 14.807> t-table 1.699 (df = 29). It can be concluded that the BEP effectively improve endurance capacity (VO2max) futsal players beginners.